1997
DOI: 10.1126/science.275.5304.1308
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Actin Stress Fibers and Focal Adhesions Enhanced by Rho-Kinase

Abstract: The small guanosine triphosphatase (GTPase) Rho is implicated in the formation of stress fibers and focal adhesions in fibroblasts stimulated by extracellular signals such as lysophosphatidic acid (LPA). Rho-kinase is activated by Rho and may mediate some biological effects of Rho. Microinjection of the catalytic domain of Rho-kinase into serum-starved Swiss 3T3 cells induced the formation of stress fibers and focal adhesions, whereas microinjection of the inactive catalytic domain, the Rho-binding domain, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
799
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,002 publications
(837 citation statements)
references
References 29 publications
34
799
1
3
Order By: Relevance
“…RhoA/Rho-associated kinase (ROCK) Recent studies have shown that the ROCK family, one of the several small GTPase Rho effectors, has major roles in actin cytoskeleton organization, 94 smooth muscle contraction 95 and gene expression. 96 Results of previous studies have shown that ROCK has a role in the contraction of vascular smooth muscle cells.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…RhoA/Rho-associated kinase (ROCK) Recent studies have shown that the ROCK family, one of the several small GTPase Rho effectors, has major roles in actin cytoskeleton organization, 94 smooth muscle contraction 95 and gene expression. 96 Results of previous studies have shown that ROCK has a role in the contraction of vascular smooth muscle cells.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…Two substrates of ROCK, myosin light chain (MLC) and myosin-binding subunit (MBS) of MLC phosphatase are thought to be important regulators of actin-myosin filament assembly (Bishop and Hall, 2000). ROCK stimulates actomyosin contractility either by direct phosphorylation of MLC or indirectly by inactivating MLC phosphatase (Amano et al, 1996(Amano et al, , 1997Kimura et al, 1996). The resulting increase in force at focal complexes triggers the transition of these structures into focal contacts.…”
Section: Cellular Mechanotransductionmentioning
confidence: 99%
“…ROCK can increase MLC phosphorylation through direct effect on MLC or indirectly by inactivating MLC phosphatase. The increased MLC phosphorylation results in stimulation of actomyosin contractility [2,55,73]. Inactivation of MLC phosphatase by ROCK plays an important physiological role such as agonist-induced Ca 2+ sensitization in smooth muscle contraction [28,29,141].…”
Section: Substrates Of Rockmentioning
confidence: 99%